The medical futility experience of nursing professionals in Greece - Polychronis Voultsos; Anna Tsompanian; Alexandra K. Tsaroucha (BMC, 2021)
Abstract Background Providing futile medical care is an ever-timely ethical problem in clinical practice. While nursing personnel are very closely involved in providing direct care to patients nearing the end of life, their role in end-of-life decision-making remains unclear. Methods This was a prospective qualitative study conducted with experienced nursing professionals from December 2020 through May 2021. Individual in-depth qualitative interviews were conducted with sixteen participants. We performed a thematic analysis of the data. Results Importantly, many participants were half-hearted in their attitude towards accepting or defining futile medical care. Furthermore, interestingly, a list of well-described circumstances emerged, under which the dying process is most likely to be a "bad and undignified" process. These circumstances reflected situations revolving around a) pain and suffering, b) treating patients with respect, c) the appearance and image of the patient body, and d) the interaction between patients and their relatives. Fear of legal action, the lack of a regulatory framework, physicians being pressured by (mostly uninformed) family members and physicians' personal motives were reported as important reasons behind providing futile medical care. The nursing professional's role as a participant in decisions on futile care and as a mediator between physicians and patients (and family members) was highlighted. Furthermore, the patient's role in decisions on futile care was prioritized. The patient's effort to keep themselves alive was also highlighted. This effort impacts nursing professionals' willingness to provide care. Providing futile care is a major factor that negatively affects nursing professionals' inner attitude towards performing their duties. Finally, the psychological benefits of providing futile medical care were highlighted, and the importance of the lack of adequately developed end-of-life care facilities in Greece was emphasized. Conclusions These findings enforce our opinion that futile medical care should be conceptualized in the strict sense of the term, namely, as caring for a brain-dead individual or a patient in a medical condition whose continuation would most likely go against the patient's presumed preference (strictly understood). Our findings were consistent with prior literature. However, we identified some issues that are of clinical importance.